Redes sociales y su incidencia en la búsqueda de información para los periodistas del diario La Hora, regional los Ríos - Rizo Ubilla, Liliana (2018)
Social networks have become indispensable and common, since information can be provided, as well as shared. Being so common and part of the environment is of great importance that this tool becomes essential for journalists in the city of Quevedo and especially those who work in the newspaper La Hora. The problem lies in how social networks affect the obtaining of information for journalists of Diario La Hora, Regional Los Ríos, the general objective is to determine what is the incidence of social networks in obtaining information from journalists in Diario La Hora, Regional Los Ríos, year 2018. For this purpose, several research tools have been used, such as: inductive and deductive methods, and research types such as descriptive and field studies at Diario La Hora, Regional Los Ríos. For this a series of sizes is proposed in order to teach these journalists to use social networks in the best way to obtain reliable information.